2020
DOI: 10.1042/bsr20201108
|View full text |Cite
|
Sign up to set email alerts
|

An elevated monocyte-to-high-density lipoprotein–cholesterol ratio is associated with mortality in patients with coronary artery disease who have undergone PCI

Abstract: Background: The aim of this study was to investigate the association between the monocyte-to-high-density lipoprotein-cholesterol ratio(MHR) and the outcomes of patients with coronary artery disease(CAD) who were treated with percutaneous coronary intervention(PCI). Methods: A total of 5679 CAD patients from CORFCHD-PCI, a retrospective cohort study (Identifier: ChiCTR-ORC-16010153), who underwent PCI were included in the study and divided into three tertiles according to their MHR values. The primary outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Emerging data suggest that higher MHR values are associated with various diseases or organ dysfunctions, such as endothelial dysfunction in Behçet disease, the presence and severity of metabolic syndrome, polycystic ovary syndrome, cardiac syndrome X, serum albumin level saphenous vein graft disease in coronary bypass, the high SYNTAX score in patients with stable coronary artery disease, asymptomatic organ damage in patients with primary hypertension, left atrial remodeling in atrial fibrillation, abdominal aortic aneurysm size, myocardial infarction, and CVD in patients with obstructive sleep apnea syndrome (14, 15, [36][37][38][39][40][41][42][43]. It has also been shown that MHR is an independent predictor of in-hospital and long-term mortality and major adverse cardiac events in patients with acute coronary syndromes or a post-PCI status (44). Therefore, the MHR is a new prognostic marker in several CVDs, which are associated with inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging data suggest that higher MHR values are associated with various diseases or organ dysfunctions, such as endothelial dysfunction in Behçet disease, the presence and severity of metabolic syndrome, polycystic ovary syndrome, cardiac syndrome X, serum albumin level saphenous vein graft disease in coronary bypass, the high SYNTAX score in patients with stable coronary artery disease, asymptomatic organ damage in patients with primary hypertension, left atrial remodeling in atrial fibrillation, abdominal aortic aneurysm size, myocardial infarction, and CVD in patients with obstructive sleep apnea syndrome (14, 15, [36][37][38][39][40][41][42][43]. It has also been shown that MHR is an independent predictor of in-hospital and long-term mortality and major adverse cardiac events in patients with acute coronary syndromes or a post-PCI status (44). Therefore, the MHR is a new prognostic marker in several CVDs, which are associated with inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The association of HDL-c with inflammatory indices could also increase the prognostic and diagnostic values of HDL-c. For example, an index that is gaining interest is the relationship between monocytes and HDL-c. Accumulation of monocytes and reduction of HDL-C may participate in atherosclerosis and CVD. Given that the relationship between the high number of monocytes and low HDL-c levels has been reported in inflammatory disorders, the monocyte to HDL ratio could be a convenient marker to predict atherosclerosis development and progression [110][111][112].…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…Elevated MHR has been proved to be associated with many disorders such as cardiovascular diseases, metabolic syndrome (MetS), and polycystic ovary syndrome (PCOS) (Akboga et al, 2016;Uslu et al, 2018;Usta et al, 2018). Studies also investigated that increased MHR was independently related to long-term mortality in patients with coronary artery disease (CAD) who have undergone percutaneous coronary intervention (Zhang et al, 2020). MHR is also a marker that could predict the presence and progression of subclinical carotid atherosclerosis in patients with T2DM (Chen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%